The Effect of Competence, Digital Skills, Work-Life Balance, and Motivation on Employee Performance, with Work Discipline as A Mediating Variable, at The Majalengka Regency Environmental Agency - Adhinugraha, Budi; Sutisna, Deden (Journal of Economics and Business UBS, 2026)
This study aimed to determine the effects of competence, digital skills, work-life balance, and motivation on employee performance through work discipline as a mediating variable at the Majalengka Regency Environmental Agency. The study employed a quantitative approach using descriptive and verification methods. The population consisted of all 64 civil servant employees at the Majalengka Regency Environmental Agency in 2026. The sampling technique used was saturated sampling or total sampling. This study utilized primary and secondary data. Primary data were collected through questionnaires distributed to civil servant employees at the Majalengka Regency Environmental Agency. Data analysis was conducted using IBM SPSS 27 software. The hypotheses were tested using path analysis. The data analysis process began with validity and reliability tests, followed by classical assumption tests, including normality, multicollinearity, and heteroscedasticity tests. Subsequently, correlation analysis, coefficient of determination analysis, multiple linear regression analysis, partial and simultaneous hypothesis testing, and mediation testing were conducted. Based on the research results and statistical tests, competence, digital skills, work-life balance, and motivation were found to influence employee performance through the mediating role of work discipline at the Majalengka Regency Environmental Agency. This finding indicates that work discipline plays an important role in strengthening the effects of these four factors on improving employee performance and, consequently, enhancing the quality of public services.